Synthesis and Characterization of Aluminated Santa Barbara Amorphous-15 via Ultrasonic-Enhanced Hydrothermal Method: Effects of Sonication, Solvent Acidity, and Si/Al Ratio - Dini Hariyanto Putri; RR Dirgarini Julia Nurlianti Subagyono; Veliyana Londong Allo; Maykel Manawan (Chemistry Department, Faculty of Sciences and Mathematics, Diponegoro University, 2025)
Aluminated Santa Barbara Amorphous-15 (Al-SBA-15) materials were successfully synthesized using an ultrasonic-enhanced hydrothermal method. The synthesis was conducted by varying the mole ratio of Si precursor and Al precursor (10 and 20), sonication time (3 and 5 hours), and solvent type (2 M hydrochloric acid (HCl) and distilled water). The resulting materials were characterized using N2 sorption analyzer, Fourier Transform Infrared Spectroscopy (FTIR), Small-Angle X-ray Diffraction (SAXRD), Scanning Electron Microscopy (SEM), and Ammonia-Temperature Programmed Desorption (NH3-TPD). FTIR spectra confirmed the presence of siloxane, silanol, and hydroxyl functional groups in all Al-SBA-15 samples. SAXRD analysis showed three characteristic peaks of SBA-15, indicating a two-dimensional hexagonal structure (p6mm). Increasing the sonication time enhanced the surface area from 718 to 767 m2/g, while reducing the pore diameter from 5.96 to 4.81 nm and the pore volume from 1.07 to 0.92 cm3/g. Raising the Si:Al molar ratio slightly increased the surface area (718 to 722 m2/g) and decreased the pore diameter and volume. Additionally, using distilled water instead of 2 M HCl as the solvent raised the surface area from 722 to 785 m2/g, while decreasing the pore diameter from 5.61 to 5.05 nm and slightly lowering the pore volume. The acidity of the Al-SBA-15 material varied according to the sonication time and the amount of Al precursor used, suggesting the potential of regulating the acidic properties through optimization of the synthesis parameters.